Viscoelastic adhesive interfacial model and experimental characterization for interfacial parameters - Wang, J.; Qin, Q.H.; Kang, Y.L.; Li, X.Q.; Rong, Q.Q. (Mechanics of materials, 2010)
In this paper, a three-parameter interfacial model based on Needleman’s cohesive theory is presented to characterize the viscoelastic mechanical properties of adhesive structures. For most adhesive structures, the mechanical behavior of adhesive interface layer can be simulated by the proposed adhesive interfacial model. To evaluate effectively the materials parameters of the adhesive layer an improved experiment-based identification method is proposed including four major steps: (1) video-recorded experimental measurement, (2) numerical simulation based on the time-dependent adhesive interfacial model, (3) genetic algorithm, and (4) independent experiment verification. Using the proposed experiment-based identification method, the viscoelastic interfacial mechanical parameters of metal adhesive structures and rubber adhesive structures under tension or shear loading are determined, respectively. Based on the identified parameters, the numerical computational results are in good agreement with the independent experimental measurement results. It seems that the proposed adhesive interfacial model is effective to characterize the mechanical properties of the adhesive layer and the improved experiment-based identification method is promising in solving parameter characterization problems of complex adhesive structures.